Efficient hydrogen and deuterium permeation reduction in Al2O3 coatings with enhanced radiation tolerance and corrosion resistance. (20th September 2018) - Iadicicco, D.; Bassini, S.; Vanazzi, M.; Muñoz, P.; Moroño, A.; Hernandez, T.; García-Cortés, I.; Sánchez, F.J.; Utili, M.; García Ferré, F.; Di Fonzo, F.
Abstract: One of the major bottlenecks in the development of the breeding blanket of the DEMO fusion reactor is the suppression of tritium permeation through structural steels as well as their protection against dissolution-corrosion by interaction with high temperature heavy liquid metals. Reduction of tritium permeation and corrosion of structural steels are crucial issues in order to enhance reactor safety and avoid operational implications. As a solution to these two daunting challenges, we developed multifunctional alumina coatings capable to tackle, at the same time, tritium permeation and Pb–Li corrosion. The coatings are deposited by pulsed laser deposition and are essentially amorphous, with nanocrystalline inclusions. By optimizing the deposition process, we provide experimental evidence that PLD-grown alumina yields a permeation reduction factor for hydrogen and deuterium well above 10 4, even after electron irradiation, and a suitable protection against corrosion by the Pb–16Li eutectic. Given these results, the multifunctional, PLD-grown alumina coatings stand out as a viable solution to some of the long-lasting issues related to fusion technologies.